Connectivity Between Coastal and Oceanic Zooplankton From Rio Grande do Norte in the Tropical Western Atlantic - Neumann Leitão, Sigrid; Melo Junior, Mauro de; Porto Neto, Fernando de Figueiredo; Silva, Andréa Pinto; Diaz, Xiomara Franchesca Garcia; Silva, Tamara de Almeida e; Nascimento Vieira, Dilma Aguiar do; Figueiredo, Lucas Guedes Pereira; Costa, Alejandro Esteweson Santos Faustino da; Santana, Jana Ribeiro de; Campelo, Renata Polyana de Santana; Melo, Pedro Augusto Mendes de Castro; et al. (Frontiers in Marine Science, 2019)
The zooplankton off the coast of Rio Grande do Norte, Brazil was studied during four oceanographic campaigns from July 2002 to May 2004. A Bongo net (mesh sizes of 64 m, 120 m, and 300 m) was used for sample collections. A total of 462 zooplankton samples was studied. These samples were classified in four areas (Coastal, Inner Shelf, Shelf Break, Slope) according to local depth and distance from coast. Most of the studied environment is oligotrophic, under the Tropical Water mass influence. We recorded 199 zooplankton taxa, and Copepoda was the most numerous with the highest number of species. There were 93 species of copepods, of which calanoids comprised 62%. The most frequent zooplankton taxa were Undinula vulgaris, Nannocalanus minor, Oithona nana, Onychocorycaeus giesbrechti, Crustacea nauplius, Bivalvia, and Gastropoda veligers. The species diversity varied from 0.87+0.28 bits ind-1 (Coastal) to 3.96+0.12 bits ind-1 (Slope). The minimum density was 11.5 ind m-3 (macrozooplankton, Inner Shelf), and the maximum density was 161.6 x 106 ind m-3 (microzooplankton, Coastal). The biomass decreased sharply between the microzooplankton to macrozooplankton fractions. The community presented a general trend in species composition that included coastal eutrophic indicators and oceanic oligotrophic indicators, with low numerical abundance of zooplanktonic organisms. A higher density occurs in the coastal area that is near the littoral area due to the continental flux and benthic regeneration. The seasonal effect was also highlighted as an important factor responsible for the dissimilarity of zooplankton communities. Cluster analysis of the samples based on Copepoda presented differences among the four campaigns corresponding to the rainy and dry seasons. The copepod’s functional traits divided the community into three groups, and the reproduction and the trophic strategies were the main factors in structuring the community. We found a pelagic gradient for the zooplankton community varying from a low diverse eutrophic coastal area to a high diverse oligotrophic oceanic area, located over a varied, high biomass benthic habitat, which is mostly covered by calcareous algae functioning on the shallow shelf as a large reef system.